Effect of benzothiadiazole treatment on improving the mitochondrial energy metabolism involved in induced resistance of apple fruit during postharvest storage. (1st January 2020) - Li, Shenge; Jiang, Hong; Wang, Yi; Lyu, Liang; Prusky, Dov; Ji, Yan; Zheng, Xiaolin; Bi, Yang
Highlights: Benzothiadiazole (BTH) inhibited blue mould rot caused by P. expansum in apple fruit. BTH enhanced adenosine triphosphate level via mitochondrial energy metabolism in apple fruit. BTH maintained the number and structure of mitochondrion in apple fruit. BTH induced the disease resistance in apple fruit during postharvest. Abstract: The effects of benzothiadiazole (BTH) on Penicillium expansum development, mitochondria energy metabolism, and changes in the number and structure of mitochondria in apple fruit were investigated after the fruit were immersed in 100 mg L −1 BTH for 10 min and then stored at 22 °C. The results indicated that BTH treatment significantly decreased the lesion diameter of fruit challenged with P. expansum ; further, treatment enhanced the activities of mitochondrial respiratory metabolism-related enzymes, such as succinate dehydrogenase, cytochrome oxidase, H + -ATPase and Ca 2+ -ATPase, along with high ATP level and energy status in apple fruit during storage. Moreover, transmission electron microscopy results indicated that BTH treatment was beneficial for maintaining the number and structure of mitochondria during storage. The results suggested that BTH treatment enhanced ATP levels via mitochondrial energy metabolism, which might contribute to the induced resistance in apple fruit during storage.